IDDF2019-ABS-0264 Hepatic cell cycle-related kinase shapes a metastatic-prone liver microenvironment via crosstalk between myeloid-derived suppressor cell and natural killer T cell. (June 2019) - Zeng, Xuezhen; Zhou, Jingying; Xiong, Zhewen; Sun, Hanyong; Yang, Weiqin; Tang, Wenshu; Feng, Yu; Cheng, Alfred
Abstract : Background: Metastasis is a prominent cause of cancer-related death governed by both cancer cell-intrinsic mechanisms and extrinsic microenvironment. Clinical observations demonstrated liver as a common metastatic site for various cancers, which may be due to its immune tolerant environment. Myeloid-derived suppressor cell (MDSC) is a heterogeneous cell population of immature myeloid cells that contribute to the formation of a favorable metastatic environment partially via suppression of immune effector cells. However, the underlying mechanisms in liver tropism of tumor metastasis remain poorly understood. We have previously discovered that cell cycle-related kinase (CCRK) can promote primary hepatocellular carcinoma (HCC) development via MDSCs. Here we hypothesize that the accumulation of hepatic MDSCs induced by CCRK may contribute to the formation of a favorable metastatic liver microenvironment. Methods: We constructed a liver-specific CCRK inducible transgenic (TG) mouse model by a Cre/loxP system. Orthotopic and metastatic mouse models were used to investigate the role of CCRK in promoting tumor growth and metastasis. PMN-MDSC was depleted by anti-Ly6G antibody. Cytokine, chemokine, and immune cells profiling were performed after sacrifice. Results: Induction of CCRK expression by tamoxifen injection could increase CD11b + Gr-1 + Ly6G + Ly6C low polymorphonuclear (PMN)-MDSCs liver accumulation specifically in male mice with upregulated Cxcl1 and Gcsf expression. Intrahepatic injection of a mouse hepatoma cell line Hep1–6 in male TG mice developed larger tumors compared to control and positively associated with increased PMN-MDSCs levels in liver. Moreover, the tumorigenicity was abolished by PMN-MDSC depletion. Notably, intrasplenic injection of a mouse melanoma cell line B16F10 exhibited an increased level of liver-infiltrating PMN-MDSCs and enhanced liver metastasis in male TG mice compared to control mice. Moreover, depletion of PMN-MDSCs suppressed metastasis in liver. Mechanistically, anti-tumor NKT cells, rather than NK cells and CD8 + T cells, were negatively correlated with tumor weight and MDSC proportion, indicating involvement of cross-talk between MDSC and NKT in liver metastasis. Conclusions: Our findings suggest that hepatic CCRK expression create a tumor growth- and metastasis-supportive liver microenvironment via enhancing immunosuppression.